Psychopathology of Criminal Women - BEHTANE, Abdelkader (Journal of Human Sciences, 2022)
If the woman is supposed to give life, not take it. Some consider female crime to be taboo, as if it conflicts with a woman’s role as a reservoir of affection. But it seems that she can change this image by turning to crime. In this context, we wonder about female crime. Why do some women resort to murder? What is the context of their crime and her psychopathology? The findings show that female crime is due to immaturity. And that, criminal women would suffer from depressive disorders, a feeling of rejection, stress, psychic trauma, etc. Generally, female crime is characterized by lower recidivism, under-representation and higher resistance to crime. Knowing that, the contexts of crime are numerous: poisoning and crimes of passion.